Long term effects of therapy among childhood cancer survivors treated in the last two decades - Duaa AbdelHameid; Alissa Mills; Jennifer Dean; Nicole Piguet; Sadhna Shankar (Elsevier, 2019)
Chemotherapy regimens have been modified over the last two decades to minimize the late effects of therapy. This study was designed to evaluate neurocognitive deficits, cardiovascular events, obesity, sexual development and bone disease among survivors of childhood cancer treated after 1990.Patient and parent questionnaires were used to prospectively collect data from childhood cancer survivors who were at least 2 years after completion of therapy or 5 years from diagnosis. Medical records were reviewed to collect data regarding diagnosis and treatment. The participants were evaluated in the clinic for physical and psychosocial late effects. Univariate and multivariate analyses were performed to identify risk factors for long-term effects of therapy.A total of 129 survivors participated in the study; 64 (50%) were females. Seventy-eight patients and 98 parents completed questionnaires. The median age at diagnosis was 4.3 years. Median time from completion of therapy to the study participation was 5.7 years. Acute lymphoblastic leukemia was the most common diagnosis (50%). Median cumulative dose of cyclophosphamide was 1,000 mg/m2 and that of anthracyclines was 123 mg/m2. A fourth of the survivors received radiation therapy. Six percent of participants were obese and 6 (4.6%) had abnormalities on echocardiogram. Thirty-six (28%) required additional resources at school. Twenty-two participants (17%) had a fracture, 18 (64%) were in patients with ALL. The diagnosis, age at diagnosis and time since completion of therapy were not associated with the outcomes of interest.Larger sample size and longer follow-up is needed to confirm these results. Keywords: Childhood cancer, Survivors, Late-effects